Effects of ospemifene on genitourinary health assessed by prospective vulvar-vestibular photography and vaginal/vulvar health indices - Goldstein, Irwin (Menopause, 2019)
OBJECTIVE: To prospectively evaluate the effects of ospemifene on the vulva and vagina in postmenopausal women using vulvar-vestibular photography and direct visual assessments. METHODS: Postmenopausal women (aged 40-80 years) with moderate to severe vaginal dryness as their most bothersome symptom (MBS) were randomized to daily ospemifene 60 mg or placebo in this 12-week, multicenter, double-blind, phase 3 study. Vulvar-vestibular photographic images were captured at baseline and week 12 and were independently assessed with the Vulvar Imaging Assessment Scale (VIAS). Changes from baseline in Vaginal and Vulvar Health Indices (VHI and VuHI) with ospemifene versus placebo were analyzed at weeks 4, 8, and 12. Correlations between VIAS, VHI, and VuHI, with vaginal dryness severity and the Female Sexual Function Index (FSFI) scores were also assessed. RESULTS: In all, 631 eligible participants were randomized (ospemifene 316, placebo 315) and included in the intention-to-treat population. Compared with placebo, ospemifene significantly improved total scores for VIAS (P = 0.0154), VHI (P < 0.0001), and VuHI (P < 0.0001) from baseline to week 12; significant VHI (P < 0.0001) and VuHI (P = 0.002) improvements were observed at week 4. Most VHI and VuHI individual items were significantly better with ospemifene versus placebo at week 12 (P < 0.05). Most correlations between the vulvovaginal assessment total scores versus vaginal dryness severity and FSFI scores were significant (P < 0.05). CONCLUSION: Improvements observed in vulvovaginal health with ospemifene assessed by prospective vulvar-vestibular photography and other direct visual assessments support its efficacy in addition to the treatment of moderate to severe vaginal dryness due to menopause and the use of photographic and direct visual evaluations in future clinical trials. Supplemental Digital Content is available in the text VIDEO SUMMARY: Supplemental Digital Content 1